Perspektif Model Bagi Hasil Laba Usaha Berbasis Syariah Pada Bumdes Sebagai Solusi Mitra Berkeadilan - Dasmi Husin; Rusydi Rusydi; Khairil Fata; Rahmi Raihan; Faisal Faisal; Indra Wijaya (Akbis: Media Riset Akuntansi dan Bisnis, 2023)
The purpose of this study was to determine the application of the sharia-based profit-sharing model to village enterprise (Bumdes) in Banna Village, Paya Punteut Village, Muara Dua District, Lhokseumawe. Along with the establishment of Bumdes in every village in Indonesia, various operational problems have arisen that threaten business continuity. On the one hand, the existence of Bumdes is very beneficial for improving the welfare of rural communities, but on the other hand it creates various new problems. One of them is the problem of financial records and business profit sharing system. Forcing a profit-sharing model like an established company certainly cannot be done as quickly as possible because the communities and characteristics of village communities are different. Therefore, we need an approach, an appropriate model, that is familiar, but does not hinder the application of financial accounting principles/standards.The research method is descriptive qualitative. This study prioritizes a participatory approach by collecting relevant information from competent sources to be discussed together through Focus Group Discussions (FGD), observation, and preparation of financial reports with a Mudharabah contract (provit sharing). The results of the study show that the application of a sharia-based profit-sharing model requires mutual consent and agreement. In principle there should be no element of coercion and all rights and obligations must be explained in a transparent manner. There is no hidden intention to benefit either party. The principles of accountability and transparency applied by Bumdes Banna Lhokseumawe must be enforced to meet the qualifications for better accounting recording and reporting. Profit sharing is good if you use profit sharing methods, but the terms must be mutually agreed upon in writing and documented.